Analisis Kebutuhan Air Bersih Dusun Waya Udara Kecamatan Tehoru Kabupaten Maluku Tengah - Juned Habel; Mujiati Mujiati; Dewi Ana Rusim; Ira Widyastuti; Davy Ivan Robert Jansen (Fakultas Teknik Universitas Cenderawasih, 2024)
The need for clean water increases every year, this is due to an uncontrolled increase in population growth so that the population is directly proportional to water needs. The problem of increasing water availability and demand due to the impact of uncontrolled population growth is also felt in Waya Udara Hamlet, Tehoru District, Central Maluku Regency. The reservoir clean water distribution network system was built to meet the clean water needs of the people of Waya Udara Hamlet at that time, but with the population growth that increased the need for clean water, so residents looked for other ways to meet clean water needs This research uses a type of quantative research with a descriptive method that aims to find facts that actually occur in the field. In this study, the study population was all heads of families in Waya Udara Hamlet, Tehoru District, Central Maluku Regency. The number of households in the village is 90 households. Analysis and Assessment of Community Satisfaction Level with Clean Water Service Distribution Service quality is one of the techniques for measuring the level of satisfaction. The results of the analysis of the level of satisfaction with the clean water service of Waya Udara Hamlet through the results of questionnaires for satisfaction, from the aspects of taste, color, smell, taste and turbidity are very satisfying. From the aspect of needs, water discharge, water tariffs are also very satisfied with the average satisfaction with needs and availability as well as tariffs and water discharge because of the results of the analysis of availability and needs. for the analysis of the availability and need for clean water of Waya Udara Hamlet in 2023 is 47.79 m3 / day for the needs of a population of 354 people and for the projection of the next 10 years in 2033 with a population of 496 people requires water as much as 66.9 m3 / day based on the discharge availability at the source is 4.97 liters / second with 1 hour filling the reservoir bath is 17.89 m3 / hour with the filling time for the reservoir for 100 m3 / day is 5.89 hours / m3 / tub. From the results of the analysis, it can be seen that the availability is greater than the need for projections for the next 10 years and from the results of the analysis on SPSS-22 the level of satisfaction with the use of clean water in the Waya Udara Hamlet Community is satisfactory because the availability and need for water are met.